La mise en œuvre de la CIF dans le Système Éducatif Portugais: sa pertinence selon le point de vue de professionnels de l’éducation. - Candeias, A.A. (2014)
Based on the recent change of the Portuguese legislation for the assessment of pupils with special education needs (SEN), this study aims to understand the implementation of the International Classification of Functioning, Disability and Health (ICF) in the Portuguese educational system. We have three objectives in mind: to know the needs of developing professionals’ competences; to characterize the practices of assessment and intervention of pupils with special educational needs required to those professionals; to reflect upon the impact on the quality of institutional responses. For this study, we adopt a qualitative and exploratory methodology that focalizes on the case of three schools in the Alentejo region, comprising kindergarten, elementary and secondary education. Based on the content analysis of collected data, a panel of four judges identifies four categories: staff training, teamwork, impact, and process of evaluation–intervention. Finally, we concluded that for the effective and efficient implementation of the ICF, it is necessary to develop staff training, especially on the assessment of functioning in pupils with special educational needs, teamwork and time management, because this new model requires new skills.